Land and Freedom : the MST, the Zapatistas and Peasant Alternatives to Neoliberalism - Vergara-Camus, Leandro (Zed Books, 2014)
The Zapatistas of Chiapas and the Landless Workers Movement (MST) of Brazil are often celebrated as shining examples in the global struggle against Neoliberalism. But what have these movements achieved in more than two decades of resistance and can any of these achievements realistically contribute to an alternative development future? Through a perfect balance of grassroots testimonies, participative observation and consideration of key development and critical political economy debates, Land and Freedom compares, for the first time, the Zapatista and MST movements. Casting a spotlight on their resistance to globalising market forces Vergara-Camus gets to the heart of how these movements organise themselves and how the decommodification of social relations is key to understanding their radical development potential. -- Provided by publisher.